Dietary supplementation with mung bean coat alleviates the disorders in serum glucose and lipid profile and modulates gut microbiota in high‐fat diet and streptozotocin‐induced prediabetic mice. Issue 9 (9th August 2021) - Hou, Dianzhi; Zhao, Qingyu; Chen, Borui; Ren, Xin; Yousaf, Laraib; Shen, Qun
Abstract : Abstract: As amajor by‐product of mung bean processing, mung bean coat (MBC), which is rich in polyphenols and dietary fiber, is deemed to be mainly responsible for the health benefits of mung bean. However, its beneficial effects on the hyperglycemia, hyperlipidemia, and gut microbiota composition in prediabetic mice is not fully understood. The objective of this study was to investigate the efficacy of MBC in alleviating high‐fat diet and streptozotocin‐induced prediabetes. Herein, compared with the model control, dietary supplementation with MBC (3%, w/w) for 12 weeks significantly decreased the fasting blood glucose (24.60%), total cholesterol (15.72%), triglyceride (14.41%), and low‐density lipoprotein cholesterol (22.45%). Furthermore, the improvements in glucose tolerance were reflected in the reduction of the area under the curve (AUC) and incremental AUC by approximately 23.08% and 51.18%, respectively. 16S rRNA gene sequencing of fecal microbiota suggested that MBC promoted the enrichment of beneficial bacteria ( Roseburia and Bifidobacterium ) and the production of short‐chain fatty acids. All of the results from this study provided a scientific reference for avoiding the functional ingredients waste of MBC and expanding its application value.